Analysis of Grammar Needs in the University Environment: A Case Study of Non-English Study Program Students at PGRI Palembang University - Ngindom, Wahid Ibrahim Banul; Joyoatmojo, Soetarno; Suryani, Nunuk; Rochsantiningsih, Dewi (Proceedings International Conference on Education Innovation and Social Science, 2023)
The study aims to analyze grammar needs in the university environment of PGRI Palembang, with a focus on non-English Study Program students. A good understanding of grammar is essential in language learning, especially in an academic context. The research was conducted to determine specific grammar needs that should be emphasized in the English course curriculum in order to improve students’ ability to use English effectively and accurately. The research method used in this study is qualitative research. Data is collected through structured interviews with lecturers and students of the Non-English Studies Program. In addition, document analysis such as the English course curriculum is also carried out to complement the data obtained. The results show that there are some grammar needs that need to be taken into account in the curriculum of English courses at this university. Primary needs include an understanding of basic grammar, the proper use of tensions, the correct use of articles and prepositions, as well as the mastery of complex sentence structures. Students also expressed the need for improved skills in using grammar contextually. This study concluded that grammar needs in the PGRI university environment of Palembang, in particular in the Non-English Studies Program, should be well identified to ensure effective learning. The curriculum should be designed in such a way that it meets the student’s grammar needs comprehensively, covering basic grammatical understanding to the use of grammar in an academic context. It can help students improve their English skills and prepare them to face language demands in their future careers.